Engineering naturally occurring CD7− T cells for the immunotherapy of hematological malignancies - Freiwan, Abdullah; Zoine, Jaquelyn T.; Crawford, Jeremy Chase; Vaidya, Abishek; Schattgen, Stefan A.; Myers, Jacquelyn A.; Patil, Sagar L.; Khanlari, Mahsa; Inaba, Hiroto; Klco, Jeffery M.; Mullighan, Charles G.; Krenciute, Giedre; et al. (Blood, 2022)
AbstractChimeric antigen receptor (CAR) T-cell therapy targeting T-cell acute lymphoblastic leukemia (T-ALL) faces limitations such as antigen selection and limited T-cell persistence. CD7 is an attractive antigen for targeting T-ALL, but overlapping expression on healthy T cells leads to fratricide of CD7-CAR T cells, requiring additional genetic modification. We took advantage of naturally occurring CD7− T cells to generate CD7-CAR (CD7-CARCD7−) T cells. CD7-CARCD7− T cells exhibited a predominantly CD4+ memory phenotype and had significant antitumor activity upon chronic antigen exposure in vitro and in xenograft mouse models. Based on these encouraging results, we next explored the utility of CD7− T cells for the immunotherapy of CD19+ hematological malignancies. Direct comparison of nonselected (bulk) CD19-CAR and CD19-CARCD7− T cells revealed that CD19-CARCD7− T cells had enhanced antitumor activity compared with their bulk counterparts in vitro and in vivo. Lastly, to gain insight into the behavior of CD19-CAR T cells with low levels of CD7 gene expression (CD7lo) in humans, we mined single-cell gene and T-cell receptor (TCR) expression data sets from our institutional CD19-CAR T-cell clinical study. CD19-CARCD7lo T cells were present in the initial CD19-CAR T-cell product and could be detected postinfusion. Intriguingly, the only functional CD4+ CD19-CAR T-cell cluster observed postinfusion exhibited CD7lo expression. Additionally, samples from patients responsive to therapy had a higher proportion of CD7lo T cells than nonresponders (NCT03573700). Thus, CARCD7− T cells have favorable biological characteristics and may present a promising T-cell subset for adoptive cell therapy of T-ALL and other hematological malignancies.